Intra-household Time Allocation: Gender Differences in Caring for Children - Inmaculada García; José Alberto Molina; Víctor M. Montuenga (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Der vorliegende Beitrag untersucht auf Basis von Daten des Sozio-oekonomischen Panels für Deutschland (SOEP), inwieweit selbständige Ausländer in Deutschland überdurchschnittlich hohe Einkommen erzielen. Die Untersuchung zeigt, dass ausländische Selbständige insgesamt höhere Einkommen erzielen als angestellt tätige Ausländer und dass der Unterschied größer ist als bei Selbständigen deutscher Nationalität. Die Konsequenzen dieser Untersuchungsergebnisse für Wirtschaftspolitikund Gründungslehre werden diskutiert. Die Ergebnisse der Untersuchung zeigen differenzierten Forschungsbedarf im Hinblick auf unterschiedliche Optionen der Entrepreneurship Education. This paper analyses the intra-household allocation of time to show gender differences in childcare. In the framework of a general efficiency approach, hours spent on childcare by each parent are regressed against individual and household characteristics, for five samples (Denmark, France, Germany, Italy and Spain), with data being drawn from the European Community Household Panel-ECHP (1994-2001). Empirical results show a clear inequality in childcare between fathers and mothers, with this being more evident in Mediterranean countries. Panel data estimates reveal that, in general, caring tasks are mainly influenced by the presence of young children in the household, by the total non-labor income, and by the ratio of mothers' non-labor income to family's non-labor income, with this latter variable exhibiting a different behavior across genders and across countries.
Keywords: D13; J22; C33; 330; Childcare; gender differences; intra-household allocation; time use